The relationship between workload pressure, performance pressure and job insecurity with job stress among employee in private sector in Melaka - Mohd Noh, Nur Syafika (2019)
Job stress has been a worldwide major challenge to the worker’s health and the healthiness of the organization itself. It has been the major problem to the organization to overcome the job stress among the employee in the organization the reason for the stress to occur can be because of the outside of work factors. However, the organizations or the employers may not be able to protect workers from stress arising outside of work, but they can protect the employee from stress that arises through work. Stress can be a biggest problem to the organization as when the worker who are stressed, they will more likely to be unhealthy, unmotivated and less productive. There for the best prevention of the stress is good management and a good work organization. besides, the employer’s need to know how to help and always be aware of what make the employee stress at work. The purpose of this study is basically to know the antecedent of employee job stress in the organization. There are several reasons that can be the factors of employee job stress in the workplace. However, this research focusing only for the factors that are possible to be the independent variable for the job stress to employee which is, the workload pressure, performance pressure and the job insecurity. This research is a quantitative type of research which has been using the questionnaire to collect all the data that required. Total data that has been collected from the respondent is at a percentage of 84%out of 100 sample that are needed by the research. The researcher using the convenience sampling method as the population of the respondents that is among the private employee in Melaka is unknown. Then, the data will be evaluated by using the SPSS (Statistical Package for the Social Science). The result will show whether there is a relationship between the Workload Pressure, performance pressure and the job insecurity towards job stress.